The Journal Investigación y Educación en Enfermería is Indexed in PubMed Central - María de los Ángeles Rodríguez-Gázquez (Investigación y Educación en Enfermería, 2021)
As Editor, it is a joy to share with you the great news that the journal Investigación y Educación en Enfermería was accepted for indexation in PubMed Central (PMC), which is the world’s largest repository of knowledge on health sciences. PubMed Central has close to seven million articles in full text and in Open Access that can be recovered through the PubMed search engine.